Real-Time Telepathology Is Substantially Equivalent to In-Person Intraoperative Frozen Section Diagnosis. - Rohr, Joseph M.; Ginnebaugh, Kevin; Tuthill, Mark; Pimentel, Jason; Markin, Rodney (Archives of Pathology & Laboratory Medicine, 2024)
* Context.--Intraoperative diagnosis by frozen section is a mainstay of surgical pathology practice, providing immediate feedback to the surgical team. Despite good accuracy with modern methods, access to intraoperative surgical pathology with an appropriate turnaround time (TAT) has been a limiting factor for small or remote surgical centers, with negative impacts on cost and patient care. Telepathology offers immediate expert anatomic pathology consultation to sites without an in-house or subspecialized pathologist. Objective.--To assess the utility of live telepathology in frozen section practice. Design.--Frozen section diagnoses by telemicroscopy from 2 tertiary care centers with a combined 3 satellite hospitals were queried for anatomic site, TAT per block, pathologist, and concordance with paraffin diagnosis. TAT and concordance were compared to glass diagnoses in the same period. Results.--For 748 intraoperative diagnoses by telemicroscopy, 694 had TATs with a mean of 18 minutes 56 seconds ± 8 minutes 45 seconds, which was slower than on glass (14 minutes 25 seconds ± 7 minutes 8 seconds, P < .001). Twenty-two (2.89% of available) were discordant, which was not significantly different from the onglass rate (P = .44) or categorical distribution (P = .31). Two cases (0.27%) had technical failures. Conclusions.--Although in-person diagnoses were statistically faster, the great majority of telemicroscopic diagnoses were returned in less than 20 minutes. This remained true through numerous pathologists, pathology assistants and/or technicians, different hospitals, and during a combined 6 years. The concentration of discordant diagnoses among relatively few pathologists suggests individual comfort with telepathology and/or frozen section diagnosis. In rare cases, technical issues prevented telemicroscopic diagnosis. Overall, this justifies continued use and expansion of telemicroscopic services in primary intraoperative diagnoses.